Anesthetic-Induced Oxidative Stress and Potential Protection - Cheng Wang; Xuan Zhang; Fang Liu; Merle G. Paule; William Slikker, Jr. (The Scientific World Journal)
Prolonged exposure of developing mammals to general anesthetics affects the N-methyl-D-aspartate (NMDA)–type glutamate or γ-aminobutyric acid (GABA) receptor systems and enhances neuronal toxicity. Stimulation of immature neurons by NMDA antagonists or GABA agonists is thought to increase overall nervous system excitability and may contribute to abnormal neuronal cell death during development. Although the precise mechanisms by which NMDA antagonists or GABA agonists cause neuronal cell death are still not completely understood, up-regulation of the NMDA receptor subunit NR1 may be an initiative factor in neuronal cell death. It is increasingly apparent that mitochondria lie at the center of the cell death regulation process. Evidence for the role of oxidative stress in anesthetic-induced neurotoxicity has been generated in studies that apply oxidative stress blockers. Prevention of neuronal death by catalase and superoxide dismutase in vitro, or by M40403 (superoxide dismutase mimetic) in vivo, supports the contention that the involvement of reactive oxygen species (ROS) and the nature of neuronal cell death in rodents is mainly apoptotic. However, more evidence is necessary to in order verify the role of the NMDA receptor subunit NR1 and ROS in anesthetic-induced neurodegeneration.